Germination and growth of Porcelia mediocris and Compsoneura trianae in Arosemena Tola, Napo, Ecuador - Abril-Saltos, Ricardo Vinicio (2024)
Introduction. Wild species are important in the ecosystem, and their preservation requires the development of effective techniques. Objective. To determine the in situ and ex situ germination characteristics and field growth of Porcelia mediocris N.A. Murray and Compsoneura trianae Warb. in Arosemena Tola, Napo, Ecuador. Materials and methods. The study was carried out between 2019 and 2020, with seeds collected from the primary forest of P. mediocris and C. trianae. Germination tests were conducted in a greenhouse and in the primary forest, measuring seed emergence, tray growth, and performing an analysis of variance between the testing sites. Seedlings were transplanted into three different soil covers at the Amazon Center for Teaching, Research, and Productivity, with measurements taken for height, stem diameter, number of leaves, and survival. Growth curves were created, and an analysis of variance was performed on the final growth measurements among the different soil covers. Results. For P. mediocris, greenhouse-grown plants showed fewer days to the emergence (67.6), but those grown under guabas cover had a greater height (19.45 cm) and germination percentage (70 %) at end of the trial. For C. trianae, plants grown at the collection site had greater height (13.38 cm) and number of leaves at the end of the evaluation. Field growth did not show differences between soil covers, with survival rate of 47 % for P. mediocris and 75 % for C. trianae. Conclusions. P. mediocris showed better germination percentages under guabas cover, while C. trianae exhibited greater growth in the primary forest, with the germination site not affecting post-transplant growth for either species.